2014
DOI: 10.1136/bmj.g3804
|View full text |Cite
|
Sign up to set email alerts
|

Relation of completeness of reporting of health research to journals' endorsement of reporting guidelines: systematic review

Abstract: Objective To assess whether the completeness of reporting of health research is related to journals' endorsement of reporting guidelines. Design Systematic review.Data sources Reporting guidelines from a published systematic review and the EQUATOR Network (October 2011). Studies assessing the completeness of reporting by using an included reporting guideline (termed "evaluations") (1990 to October 2011; addendum searches in January 2012) from searches of either Medline, Embase, and the Cochrane Methodology Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
184
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(198 citation statements)
references
References 157 publications
(171 reference statements)
6
184
1
7
Order By: Relevance
“…In medicine there is strong evidence for the effectiveness of CONSORT guidelines -journals that do not endorse the CONSORT statement show poorer reporting quality compared with endorsing journals 79 . For the ARRIVE (Animal Research: Reporting of In Vivo Experiments) guidelines 80 , studies comparing the reporting of ARRIVE items in specific fields of research before and after the guidelines were published report mixed results [81][82][83] .…”
Section: Diversifying Peer Reviewmentioning
confidence: 99%
“…In medicine there is strong evidence for the effectiveness of CONSORT guidelines -journals that do not endorse the CONSORT statement show poorer reporting quality compared with endorsing journals 79 . For the ARRIVE (Animal Research: Reporting of In Vivo Experiments) guidelines 80 , studies comparing the reporting of ARRIVE items in specific fields of research before and after the guidelines were published report mixed results [81][82][83] .…”
Section: Diversifying Peer Reviewmentioning
confidence: 99%
“…Comparisons of protocols with publications showed that most trials had at least one primary outcome changed, introduced, or omitted; and investigators of new trials rarely set their findings in the context of a systematic review 20 . Reporting guidelines such as CONSORT and PRISMA aim to improve the quality of research reports, but these guidelines should be followed much more thoroughly 67 . 55 , and the WHO has also called for public disclosure of all trials (http://www.who.int/ ictrp/results/WHO_Statement_results_reporting_ clinical_trials.pdf).…”
Section: Abuse Of Poor Reporting or No Reportingmentioning
confidence: 99%
“…Research topics include reviews of time trends in the nature and quality of publications; the development of tools and strategies to improve the planning, design, conduct, management and reporting of biomedical research; investigating strategies to help journals to improve the quality of manuscripts; and so on (e.g. Hopewell et al, 79 Stevens et al, 80 Barnes et al, 81 Mahady et al 82 ).…”
Section: Further Development Of the Equator Networkmentioning
confidence: 99%